Impact of Non-Governmental Organizations Supporting Women Entrepreneurs on Local Development - Simge Çin; Fatih Altun (Sosyal Siyaset Konferansları Dergisi)
Development is an issue on the agenda of all countries. It is generally understood that the scope of development must change over time, and sustainable development goals are set. Economic arrangements alone are insufficient for sustainable development or for increasing welfare. Making changes in the social field, the accessibility of services, and the participation of every segment in production are important points in holistic and sustainable development. Today, the most commonly used developmental approaches are multi-actor. As one such actor, non-governmental organizations (NGOs) specialize in their specific fields and provide support where the state cannot. However, NGOs are not simply actors supporting the state; they act as main actors as well. It can be difficult for state administrations to reach local environments, limiting the ability to deliver services, allowing NGOs a role in providing services and contacting people one-to-one. NGOs support development at all levels through the projects they carry out. On the other hand, integrating women into development and supporting women entrepreneurs enables the majority of the population to participate in production for both the development of women’s social status and the sustainability of development. This study evaluates the impact of NGOs supporting women entrepreneurs on local development. In this context, the activities of three NGOs, which are outstanding for their support of women’s entrepreneurship, are examined, namely, KAMER (Women’s Center), KAGIDER (The Women Entrepreneurs Association of Turkey), and KEDV (Foundation for the Support of Women’s Work). The impact of NGOs on women entrepreneurs on local development is discussed.